From Ekstrem Kanan to Kadrun: A Semantic History of Islamic Stigma in Political Dynamics in Indonesia - Winarti, Murdiyah; Fauzi, Wildan Insan; Kusmarni, Yani; Santosa, Ayi Budi; Tarunasena, Tarunasena (History Department, Semarang State University and Historian Society of Indonesia, 2024)
Abstract: This article tries to analyze several terms that indicate a stigma againsts Islamic politics in Indonesia, such as right-wing extrimist, jihad commando, and kadrun. Kadrun is the newest form to stigmatize Islam in Indonesia, so it is interesting to review. Stigma against Islam can arise due to three main points, namely: the misunderstanding of Islam because of how it was represented according to the Orientalism point of view, the mainstream media framing, and the “terrorist” attack of the Western world. The research uses a historical approach that identifies various terms of stigma against Islam in the archives. Archives regarding the protest in Java in the 20th century were used to identify the stigma attached to Islam at the end of the colonial period. The archives at MUI (Indonesian Council of Ulama) were used to see the relationship between the terms right-hand extremist and jihad commando in the dynamics of relations between Islam during the New Order Era. Content analysis method and Twitter “crawling” data collection techniques were used to describe the kadrun concept. The results of research on the words right-hand extremist, jihad commando, and kadrun put Islam as a political doctrine, which was the opposition to the ruling government. Historical analysis shows that the stigma against political Islam has been a recurring phenomenon since the Dutch East Indies era, which continued to this era and might continue as a vicious cycle of conflict in Indonesia. Abstrak: Artikel ini mencoba menganalisis beberapa istilah yang mengindikasikan adanya stigma terhadap politik Islam di Indonesia, seperti ekstrimis kanan, komando jihad, dan kadrun. Kadrun merupakan bentuk terbaru dari stigma terhadap Islam di Indonesia, sehingga menarik untuk diulas. Stigma terhadap Islam dapat muncul karena tiga hal utama, yaitu: kesalahpahaman terhadap Islam karena direpresentasikan menurut sudut pandang Orientalisme, framing media arus utama, dan serangan “teroris” dari dunia Barat. Penelitian ini menggunakan pendekatan historis yang mengidentifikasi berbagai istilah stigma terhadap Islam dalam arsip. Arsip-arsip mengenai protes di Jawa pada abad ke-20 digunakan untuk mengidentifikasi stigma yang dilekatkan pada Islam pada akhir masa kolonial. Arsip-arsip di MUI (Majelis Ulama Indonesia) digunakan untuk melihat hubungan antara istilah ekstremis kanan dan komando jihad dalam dinamika relasi Islam selama masa Orde Baru. Metode analisis isi dan teknik pengumpulan data “crawling” Twitter digunakan untuk mendeskripsikan konsep kadrun. Hasil penelitian terhadap kata ekstremis kanan, jihad komando, dan kadrun menempatkan Islam sebagai doktrin politik yang menjadi oposisi bagi pemerintah yang berkuasa. Analisis historis menunjukkan bahwa stigma terhadap Islam politik telah menjadi fenomena yang berulang sejak era Hindia Belanda, yang berlanjut hingga era sekarang dan mungkin akan terus berlanjut sebagai lingkaran setan konflik di Indonesia.